Are humanities forever the bridesmaid to STEM’s bride? : outcomes of the Finnish research funding model 2013-2016 for the humanities and STEM fields - Kolesnikovich, Victoria (2019)
The primary aim of this thesis is to see whether the outcomes of Finnish research-funding model, which was active during the years 2013-2016, is similar for STEM fields and the Humanities. The goal is to see whether this funding model unintentionally prioritises research in STEM field and overlooks the Humanities’ research. The study uses the theory of disciplinary differences (Becher 1989) and the conception of Knowledge Economy to explain the outcomes for STEM fields and the Humanities in the Finnish research-funding model, which was in place during the years 2013-2016. The data includes an overview of research policies from the years 2011-2016; a part of the funding model, which deals with research, and a numerical dataset, which corresponds to each studied component of the funding model (overall 5 components). The results indicated that in the category of scientific publications STEM fields find themselves in a more privileged position than the Humanities due to their publication patterns. Therefore, it is possible to say that the funding model 2013-2016 unintendedly advances STEM fields in this category. However, the findings from four other categories did not come to produce direct answers to the research questions but served as a rich source of background information for this study.